Reviewer Acknowledgement 2013 - Stahel, Philip F (BioMed Central, 2014)
CONTRIBUTING REVIEWERS: The Editors of Patient Safety in Surgery would like to thank all our reviewers who have contributed to the journal in Volume 7 (2013).